2020
DOI: 10.1002/ange.201913069
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective N‐Alkylation of Indoles in Aqueous Microdroplets

Abstract: Many reactions showmuchfaster kinetics in microdroplets than in the bulk phase.M ost reported reactions in microdroplets mirror the products found in bulk reactions. However,t he unique environment of microdroplets allows different chemistry to occur.I nt his work, we present the first chemoselective N-alkylation of indoles in aqueous microdroplets via athree-component Mannich-type reaction without using any catalyst. In sharp contrast, bulk reactions using the same reagents with ac atalyst yield exclusively C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The protonated carbon dioxide and deprotonated amine reactions are of special interest because these forms of the reagents could arise from superacid/superbase reactions at the interface as discussed in the Introduction. 28 Previous reports 28,[30][31][32][33][34] have suggested that superacid (extreme pH) at the interface of organic droplets (and dielectric layers at the interface of water microdroplets) accelerate reactions. These results indicated the importance of water, even traces of water 28 in interfacial microdroplet chemistry.…”
Section: Further Mechanistic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protonated carbon dioxide and deprotonated amine reactions are of special interest because these forms of the reagents could arise from superacid/superbase reactions at the interface as discussed in the Introduction. 28 Previous reports 28,[30][31][32][33][34] have suggested that superacid (extreme pH) at the interface of organic droplets (and dielectric layers at the interface of water microdroplets) accelerate reactions. These results indicated the importance of water, even traces of water 28 in interfacial microdroplet chemistry.…”
Section: Further Mechanistic Considerationsmentioning
confidence: 99%
“…[26][27][28] Most studies of reaction acceleration have been done in organic solvents but aqueous droplet reactions are also well represented. [29][30][31][32][33] Active species generated in the dielectric layer at the surface of water microdroplets include free radicals and hydrogen peroxide. 29,30,34 In very signicant work, the strong electric eld at the surface of aqueous droplets was recognized as playing a crucial role in reaction acceleration due to hydronium and hydroxide ion formation by ready autoionization of water at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was surprisingly observed that several reactions in microdroplets followed a different pathway from the bulk. A typical example is chemoselective N ‐alkylated indoles in microdroplets without any catalysts in comparison with the formation of C ‐alkylated indoles in the corresponding bulk reactions [34] . Similar extraordinary transformation pathways including the formation of gold and N ‐heterocyclic carbenes, [35] cyclic reaction by dual Schiff reactions, [36] and ester hydrolysis [37] have also been discovered by microdroplet reactions.…”
Section: Introductionmentioning
confidence: 90%
“…Soon later Gnanamani et al. achieved chemoselective N ‐alkylation of indole in aqueous microdroplets through a three‐component Mannich‐type reaction [34] . In sharp contrast, the bulk reaction using the same reagents and catalysts only produces C ‐alkylation products.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the change in reaction products against time (µs to ms) between the formation of the charged droplet and its introduction into the mass spectrometer showed that charged droplets help accelerate chemical reactions, including the formation of hydrazine 196) , the demetallation of chlorophyll 197) , Hantzsch synthesis 198) , catalyst-free Nalkylation of indole 199) , synthesis of ribonucleosides 200,201) , acid-induced unfolding of cytochrome c, hydrogendeuterium exchange in bradykinin 202) and angiotensin I 203) , and the Baeyer-Villiger reaction 204) . For more detailed descriptions, we refer the reader to comprehensive reviews [205][206][207] .…”
Section: Accelerating Chemical Reactions In Small Dropletsmentioning
confidence: 99%